Faktor-faktor Praktik Manajemen Sumber Daya Manusia yang Mempengaruhi Kinerja Guru - Melinda, Tina (Kajian Manajemen dan Bisnis, 2009)
The aims of the research are to analyze and prove the influence of Practice of Human Resources Management Factors to Teacher's Performance. The population of the research is Senior High School's teachers, in this research, the samples represented by Senior High School in Surabaya and Sidoarjo. The size of the sample is 12 Senior High Schools with sample collecting is area method sampling and the numbers of respondent are 48 respondents.